2021
DOI: 10.1021/acsabm.0c01668
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Dynamics of Endocytic Pathways Adapted by Small DNA Nanocages in Model Neuroblastoma Cell-Derived Differentiated Neurons

Abstract: Multiple endocytic pathways operate on the plasma membrane of cells at any moment with diverse but specific cellular functions. Knowledge of uptake of synthetic nanoparticles and ligands with respect to endocytic pathways is crucial to device the appropriate ligands for therapeutic delivery into differentiated neurons for targeting neuronal diseases. We herein explore the mechanisms of cellular uptake of 3D tetrahedral DNA nanocages at different stages of differentiating neurons. We monitored the uptake, kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Lactose is known to compete with extracellular Gal3 for binding to specific β-galactosides on the plasma membrane receptors and, therefore, used to inhibit the uptake of extracellular Gal3. 25 It was observed that the uptake of Gal3 was significantly decreased when inhibited by lactose (CIE blocker), whereas CNPs uptake was marginally affected in cells ( Figure 7c, d ). However, on inhibition via dynasore, the uptake of Gal3 was reduced only marginally.…”
Section: Resultsmentioning
confidence: 90%
“…Lactose is known to compete with extracellular Gal3 for binding to specific β-galactosides on the plasma membrane receptors and, therefore, used to inhibit the uptake of extracellular Gal3. 25 It was observed that the uptake of Gal3 was significantly decreased when inhibited by lactose (CIE blocker), whereas CNPs uptake was marginally affected in cells ( Figure 7c, d ). However, on inhibition via dynasore, the uptake of Gal3 was reduced only marginally.…”
Section: Resultsmentioning
confidence: 90%
“…Transferrin (Tf) and galectin-3 (Gal3) are classical ligands used to study the clathrin-mediated and clathrin-independent pathways, respectively. 28 Cholera toxin B-subunit (CTxB) binds to lipid GM1 on the plasma membrane and builds tubular endocytic tubules which are scissioned by cellular machinery like dynamin or actin or endophilin. These internalized vesicles then mature into early endosomes from where CTxB retrogradely transports to endoplasmic reticulum via plasma membrane and Golgi bodies 29 We compared the change in cellular internalized fractions of all the above ligands in RPE1 cells seeded over DNA HGX coated and an uncoated glass coverslip.…”
Section: Resultsmentioning
confidence: 99%
“…Transferrin (Tf) and galectin-3 (Gal3) are classical ligands used to study the clathrin-mediated and clathrin-independent pathways, respectively. 36 Cholera toxin B-subunit (CTxB) binds to lipid GM1 on the plasma membrane and builds tubular endocytic tubules that are scissioned by cellular machinery like dynamin or actin or endophilin. These internalized vesicles then mature into early endosomes from where CTxB retrogradely transports to endoplasmic reticulum via plasma membrane and Golgi bodies.…”
Section: Resultsmentioning
confidence: 99%